Coefficients of Meromorphic Bi-Bazilevic Functions. (9th March 2014) - Jahangiri, Jay M.; Hamidi, Samaneh G.
Abstract : A function is said to be bi-Bazilevic in a given domain if both the function and its inverse map are Bazilevic there. Applying the Faber polynomial expansions to the meromorphic Bazilevic functions, we obtain the general coefficient bounds for bi-Bazilevic functions. We also demonstrate the unpredictability of the behavior of early coefficients of bi-Bazilevic functions.